8 - Information and Communication Technologies in Higher Education in Africa: Initiatives and Challenges: Lishan Adam - Lishan Adam (Journal of Higher Education in Africa, 2003)
African higher education institutions are at a stage where they are striving to im- prove their information and communication technologies (ICTs) infrastructure, con- tent, and skills; making resources available to meet the growing needs of students and faculty; and responding to the pressure for effectiveness. They are also con- fronted with a dilemma of turning ongoing ICTs initiatives into opportunities and understanding what ICTs mean to the transformation of higher education in general and to research, teaching, and learning in particular. This paper examines the in- creasing role of ICTs in African higher education, ongoing initiatives, progresses made, and the dilemmas and challenges.